2018
DOI: 10.12659/msm.908814
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Transcription Factor 1 (GLCCI1) Variant Impacts the Short-Term Response to Intranasal Corticosteroids in Chinese Han Patients with Seasonal Allergic Rhinitis

Abstract: BackgroundGenetic correlations with the response to intranasal corticosteroids (INCS) in seasonal allergic rhinitis (SAR) treatment are unknown. This study aimed to evaluate the role of gene polymorphisms in the response to INCS in Chinese Han patients with moderate to severe SAR.Material/MethodsIn this study, 286 Chinese Han patients with SAR were genotyped for 4 candidate genes: the glucocorticosteroid receptor (NR3C1) gene, glucocorticoid-induced transcription factor 1 (GLCCI1) gene, T-box 21 gene (TBX21), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A study focused on the GLCCI1 genotype, rs37973 has demonstrated that AR may be insensitive to glucocorticoids due to its inherited nature [ 25 ]. This genotype has been associated with asthma patients being less sensitive to inhaled corticosteroids (ICS) [ 26 ] and AR patients being less susceptible to INCS [ 22 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study focused on the GLCCI1 genotype, rs37973 has demonstrated that AR may be insensitive to glucocorticoids due to its inherited nature [ 25 ]. This genotype has been associated with asthma patients being less sensitive to inhaled corticosteroids (ICS) [ 26 ] and AR patients being less susceptible to INCS [ 22 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the TNSS rate of change is 0.55 or higher, INCS therapy is efective; if it is below 0.55, it indicates INSC insensitivity [17,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the GLCCI1 was reported to be associated with the development of asthma. [15][16][17][18] However, there is less evidence of its association with the development of AR. Thus, our study aimed to identify whether the polymorphisms in the GLCCI1 rs37937 are associated with the development of AR in a Chinese Han population, and to assess the correlation between the gene polymorphisms and the response to INCS as well.…”
Section: Introductionmentioning
confidence: 99%